Abordagens genômica e epidemiológica da leishmaniose visceral em Campo Grande, Mato Grosso do Sul, Brasil - Alves, Natalia Oliveira (2024)
Leishmaniases constitute a group of neglected vector-borne parasitic diseases that are among the six global priorities for endemic diseases. Visceral leishmaniasis (VL) is the most severe form of the disease, characterized by systemic involvement and high mortality rates in immunosuppressed and untreated patients. Complications such as post-kala-azar dermal leishmaniasis (PKDL) and para-kala-azar dermal leishmaniasis (para-KDL) may also occur. The majority of cases are concentrated in tropical and subtropical regions, with Brazil being one of the seven countries responsible for over 90% of VL cases and recognized as endemic. Mato Grosso do Sul is an endemic area for this disease, with its capital, Campo Grande, experiencing intense transmission.The aim of this study was to analyze the epidemiological and genetic aspects of Leishmania spp. in patients diagnosed with VL at the Hospital Universitário Maria Aparecida Pedrossian of the Universidade Federal do Mato Grosso do Sul (Humap-UFMS/Ebserh), and to report atypical cases of VL, including Para-KDL. The study was conducted between August 2021 and June 2023, and included 127 patients admitted to Humap-UFMS/Ebserh with suspected VL. Bone marrow aspirate samples collected as part of routine diagnostic procedures at the hospital were subjected to additional tests at the Laboratório de Parasitologia Humana of the Instituto de Biociências da UFMS (LPH/INBIO/UFMS), including indirect parasitological diagnosis (culture) and molecular diagnosis (polymerase chain reaction, PCR). A total of 18 cultures from 17 patients were established, and the genetic material of the parasites was extracted and sent to the Laboratório de Pesquisa e Análises Genéticas da Universidade Estadual de São Paulo (PANGENE/UNESP) for next-generation sequencing (NGS) using the MiSeq Illumina platform, followed by data analysis. Additionally, clinical and epidemiological data were gathered from medical records. The study identified 40 cases of VL among the 127 patients included in the analysis. A notable prevalence of cases was observed among non-white males, with an average age of 39.7 years. Pancytopenia, smoking, and cutaneous lesions were directly associated with the disease, suggesting a potential increase in the risk of VL. Coinfection with HIV was identified in 33 of the 40 VL patients, and secondary prophylaxis was more common among those with a positive HIV status. Moreover, a notable correlation was identified between disease severity and the presence of anemia, cutaneous lesions, and pulmonary and renal diseases. Three cases were of particular interest due to the presence of clinical characteristics suggestive of para-KDL, including fever, hepatomegaly/splenomegaly, pancytopenia, and disseminated cutaneous lesions. The presence of the parasite was confirmed in cutaneous lesions and bone marrow aspirates, with L. infantum identified as the causative agent. Comorbidities, VL recurrence, and treatment regimens were described and related to the outcomes of these three cases. NGS analysis of the 18 samples revealed the presence of Leishmania species, with L. infantum identified in nine cases, L. amazonensis in one case, and the coexistence of L. amazonensis and L. infantum in eight cases. Severity and the presence of comorbidities such as HIV were more pronounced in the mixed infection group. It is of paramount importance to characterize the epidemiological profile of VL and to identify the Leishmania species and circulating strains in order to facilitate a comprehensive understanding of the disease, to enable effective monitoring, and to provide training for healthcare professionals. This enables early recognition of symptoms, improved patient follow-up, and supports public health policies to combat the disease. Additionally, this information provides a basis for identifying and intervening in atypical cases, such as those associated with para-KDL.